Development of an up-flow anoxic nano-biotechnological reactor for simultaneous removal of ammonia and COD from low C/N secondary treated wastewater. (August 2020) - Desireddy, Swathi; P.C., Sabumon; R.L., Manasa; Mehta, Alka
Graphical abstract: Highlights: Novel anoxic nano-biotechnological process for simultaneous ammonia and COD removal. The process does not require aeration, alkalinity and sludge disposal. Enhanced performance by evolving anammox in a gradient of NH4 + -N and NO2 − N. The presence of AOBs, denitrifiers and anammox species in the reactor. The process can meet stringent discharge standard as low as ≤ 10 mg N/L. Abstract: Fe 3+ reduction coupled to nitrification and Fe 2+ oxidation coupled to denitrification, occurring in anoxic sediments of aquatic ecosystems, play an important role in global nitrogen cycle. Till date, limited research was done in applying this phenomenon to wastewater treatment. In this study, we fabricated and evaluated an anoxic up-flow packed bed continuous reactor that mimics the Fe redox cycle coupled to microbial mediated simultaneous removal of NH4 + -N and COD. The process was initially developed using synthetic wastewater and was later applied to treat low C/N secondary treated wastewater generated from a conventional sewage treatment plant in Chennai, India. Studies were carried out for 500 days to evaluate the performance of the novel process using laboratory synthesized Granulated Nanoscale Oxyhydroxides of Fe (GNOF) as electron acceptor in a 3.92 L capacity anoxic up-flow packed bed reactor. The reactor was operated at different loading rates by varying the Hydraulic Retention Time (HRT) between 24 h and 4 h. Enhanced removals of NH4 + -N (93.20 ± 2.37 %), TN (86.45 ± 6.04 %), and COD (66.47 ± 13.90 %) were attained at 12 h HRT as a result of co-existence of ammonia oxidizing bacteria, denitrifiers, and anammox species. Enhanced performance was obtained by evolving anammox in a gradient of NH4 + -N and NO2 − -N in the reactor. This work demonstrates the use of GNOF for the first time in continuous packed bed reactor for the anoxic removal of NH4 + -N and COD from secondary treated wastewater. This process holds economic advantages compared to other biological nitrogen removal techniques: (i) as the requirement of oxygen is substituted by GNOF, (ii) occurrence of simultaneous nitrification and denitrification in the single reactor maintains the pH and hence alkalinity addition is not required, and (iii) sludge disposal costs are less. The recycling of GNOF inside the reactor makes this process more sustainable and suitable for practical applications.